On Inverse Form Finding for Anisotropic Elastoplastic Materials - Germain, Sandrine; Steinmann, Paul (AIP Conference Proceedings, 2011)
The goal of this contribution is to present an extension of the work of Germain et al. [1] on inverse form finding for anisotropic hyperelastic materials to the case of anisotropic elastoplastic materials formulated in the logarithmic strain space. A short review of the theoretical aspects is presented. Based on some numerical examples we show that our method for inverse form finding in elastoplasticity can be used if the plastic strains are previously given as it is the case when a desired hardening state is prescribed. © 2011 American Institute of Physics.
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-TM.oninve_3
Keywords: Anisotropy; Elastoplasticity; Inverse Form Finding; Large Strain; Logarithmic Strain